Respuesta :

gmany

Answer:

[tex]\large\boxed{for\ (-3,\ 2):\ y-2=-\dfrac{1}{5}(x+3)}\\\boxed{for\ (2,\ 1):\ y-1=-\dfrac{1}{5}(x-2)}[/tex]

Step-by-step explanation:

The point-slope form of an equation of a line:

[tex]y-y_1=m(x-x_1)[/tex]

m - slope

The formula of a slope:

[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]

========================================

We have the points (-3, 2) and (2, 1).

Substitute:

[tex]m=\dfrac{1-2}{2-(-3)}=\dfrac{-1}{5}=-\dfrac{1}{5}[/tex]

for (-3, 2)

[tex]y-2=-\dfrac{1}{5}(x-(-3))\\\\y-2=-\dfrac{1}{5}(x+3)[/tex]

for (2, 1)

[tex]y-1=-\dfrac{1}{5}(x-2)[/tex]